Ocular Pulse Amplitude in Non-Diabetic Patients with End Stage Renal Disease and Normal Individuals Using Dynamic Contour Tonometry - C P, Shimna; R, Arathi Simha; David, Vinoi George; Varughese, Santosh; Abraham, Lekha Mary (Nepalese Journal of Ophthalmology, 2019)
Introduction: Ocular Pulse Amplitude (OPA) is the fluctuation of IOP with the cardiac cycle which is equal to the difference between systolic and diastolic IOP. These variations in IOP are thought to be caused by the blood volume that is pumped into the eye, mainly the choroidal bed during each cardiac cycle. In patients with end stage renal disease (ESRD), Choroidal perfusion has been found to be reduced as determined by Indocyanine Green Angiography (ICG) which is an invasive procedure. OPA is recorded by Dynamic Contour Tonometer (DCT) which represents a potential new technology for measuring choroidal blood flow indirectly & non-invasively especially in patients with suspected compromise in perfusion as in ESRD. In this study we postulate that measurement of OPA can be used to assess the choroidal perfusion inpatients with ESRD.Objectives: To measure OPA in non-diabetic patients with ESRD on hemodialysis and to compare it with that of OPA in age matched normal individuals.Materials & Methods: It was a prospective Cross-sectional study and was done in a clinical set up during the period of January 2013 to October 2013. OPA among 44exposed and 44 non exposed individuals were measured using Dynamic Contour Tonometry (DCT) and analysis done.Results: The mean OPA in non diabetic patients with ESRD was 1.945mm Hg (CI:1.847 – 2.043) and the mean OPA in age matched normals was 2.16mm Hg (CI: 2.08– 2.24).Conclusion: OPA in non diabetic ESRD patients was statistically significantly lower than that of age matched normals (p=0.03). There was no correlation between OPA and other parameters like age, gender, intraocular pressure, blood pressure or serumcreatinine levels.